Penerapan Bimbingan Kelompok untuk Memenuhi Kebutuhan Kasih Sayang dan Rasa Memiliki pada Siswa Tingkat Sekolah Menengah Pertama (SMP) - Catherine James; Alfrida Silomba; Jisica Palondongan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The need for affection and belonging is an important aspect in the social and emotional development of students, especially at the Junior High School (SMP) level, where students are in the early adolescent phase characterized by a strong need for acceptance and recognition in the social environment. However, not all students are able to optimally fulfill these needs, so appropriate services are needed to assist them. This study aims to examine the application of group guidance in meeting the needs for affection and belonging in junior high school students. The study used a qualitative approach with a literature review method through the collection and analysis of various relevant literature sources. The results of the study indicate that group guidance is effective in providing positive social experiences for students, such as feeling accepted, appreciated, and being able to develop social and emotional skills, including empathy, cooperation, and self-confidence. Through group dynamics, students can interact, share experiences, and build better relationships with peers. The implications of this study indicate that group guidance needs to be implemented optimally and continuously as a strategic effort to support the fulfillment of the needs for affection and belonging and improve the psychological well-being of students in the school environment.